2020
DOI: 10.3389/fgene.2020.00692
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Association Study on Feed Efficiency Related Traits in Landrace Pigs

Abstract: Feed efficiency (FE) traits in pigs are of utmost economic importance. Genetic improvement of FE related traits in pigs might significantly reduce production cost and energy consumption. Hence, our study aimed at identifying SNPs and candidate genes associated with FE related traits, including feed conversion ratio (FCR), average daily gain (ADG), average daily feed intake (ADFI), and residual feed intake (RFI). A genome-wide association study (GWAS) was performed for the four FE related traits in 296 Landrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 84 publications
1
16
0
1
Order By: Relevance
“…The proposed biomarkers can be also confronted to genomic regions identified by genome-wide association study (GWAS) as affecting FE traits. For instance, TEX2 (Testis Expressed 2 protein) identified here as a predictive biomarker for RFI classification, was identified as a positional candidate in SNP detected for average daily feed intake (a FE related trait) in Landrace pigs [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proposed biomarkers can be also confronted to genomic regions identified by genome-wide association study (GWAS) as affecting FE traits. For instance, TEX2 (Testis Expressed 2 protein) identified here as a predictive biomarker for RFI classification, was identified as a positional candidate in SNP detected for average daily feed intake (a FE related trait) in Landrace pigs [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Almost all GWAS for body length, body height, and total teat number were performed by single-locus GWAS. Weighted single-step GWAS (WssGWAS) is widely used in association analysis to increase the number of genotyped animals in livestock ( Suwannasing et al, 2018 ; Lee et al, 2019 ; Fu et al, 2020 ). WssGWAS is a promising method allowing utilization of phenotypes from ungenotyped animals based on pedigree information, so we compared the result from two methods on body length, body height, and total teat number in pigs.…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of the interrelationship process among FE traits at the molecular level could provide new insights into the biological pathways involved and their genetic regulation. To date, a wide range of pathways have been associated with these traits, including forebrain development and neuron differentiation, hormone and growth factors, gluconeogenesis, lipogenesis, epithelial cell differentiation and hematopoietic cell lineage ( McKenna et al, 2018 ; Li et al, 2019 ; Fu et al, 2020 ; Lindholm-Perry et al, 2020 ; Marchesi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with a study in another farmed species, spam1 and hyal4 , both genes found within the significant QTL for FI, have been previously reported as associated with FI in Landrace pigs. The authors suggest a role of these genes in fat synthesis and in lipid associated pathways, such as transport and metabolism ( Fu et al, 2020 ). This could be explained by the fact that the amount of lipids plays a key role in the control of feed intake, as has been reported in livestock species ( Harvatine and Allen, 2006 ; Kuhla et al, 2016 ), mainly by acting on the hypothalamic signals regulating feed consumption and energy expenditure ( Allen et al, 2005 ; Relling et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%